Gagging and throttling by rice grains: An unusual case of asphyxia in the name of witchcraft - Shrestha, Ahana; Gautam, Rakshya; Ghimire, Manish (Journal of Kathmandu Medical College, 2023)
Witchcraft-related violence persists in Nepal, with accusations serving as cultural weapons against those deviating from norms, especially vulnerable individuals like the elderly, impoverished, widowed, or unmarried women. This case report aims to highlight the myths and consequences surrounding these beliefs. A 55-year-old woman, accused of witchcraft, was found dead under seven sacks of rice. Autopsy revealed death by asphyxia, caused by gagging from rice grains with throttling. This tragic incident underscores the urgent need to address and dismantle such harmful superstitions, ensuring the safety and dignity of all individuals within the community.